2014
DOI: 10.3892/etm.2014.1656
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ulinastatin administered at different time points on the pathological morphologies of the lung tissues of rats with hyperthermia

Abstract: Hyperthermia not only directly induces cell injury of body tissues, but also causes the body to release large amounts of inflammatory mediators and cells with extensive biological activities to induce a systemic inflammatory response and immune dysfunction. Thus, hyperthermia causes systemic inflammatory response syndrome, aggravating injuries to various organs. This study aimed to observe the effects of ulinastatin (UTI) administered at different time points on the cellular morphologies of the lung tissues of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, it was still higher than the control group, which indicated that miR-27b was involved in the mechanism of ALI development and downregulated miR-27b played a protective role for ALI. A relevant research presented that the breathing rate and lung tissue of W/D ratios in rats among the multifarious hyperthermia groups were dramatically higher than the normal control group, which revealed that the pulmonary water content and pulmonary vascular permeability had increased (Qin, Tian, Wu, Yu, & Guo, 2014). It has been accounted that, miRNAs as regulatory genes, can reduce the risk of various diseases as well as improve therapy by regulating other RNA molecules, and participate in some inflammatory lung disorders such as ALI (Carl, Trgovcich, & Hannenhalli, 2013;Zhou et al, 2011).…”
Section: Downregulated Mir-27b Alleviates Pathological Changes Of Ali Micementioning
confidence: 99%
“…However, it was still higher than the control group, which indicated that miR-27b was involved in the mechanism of ALI development and downregulated miR-27b played a protective role for ALI. A relevant research presented that the breathing rate and lung tissue of W/D ratios in rats among the multifarious hyperthermia groups were dramatically higher than the normal control group, which revealed that the pulmonary water content and pulmonary vascular permeability had increased (Qin, Tian, Wu, Yu, & Guo, 2014). It has been accounted that, miRNAs as regulatory genes, can reduce the risk of various diseases as well as improve therapy by regulating other RNA molecules, and participate in some inflammatory lung disorders such as ALI (Carl, Trgovcich, & Hannenhalli, 2013;Zhou et al, 2011).…”
Section: Downregulated Mir-27b Alleviates Pathological Changes Of Ali Micementioning
confidence: 99%
“…In many scientific papers the beneficial effect of the sulphureted hydrogen on the inflammated lung is presented [88,[93][94][95][96][97]. Benetti et al [88] demonstrates that through the administration of the sodium mono-hydrogen-sulphate (NaHS) that generates sulphureted hydrogen, the accumulation of neutrophils and of eosinophils is inhibited.…”
Section: Therapy With Antioxidantsmentioning
confidence: 99%
“…These findings suggest, to some extent, that intraoperative ulinastatin might promote the recovery of lung injuries caused by surgery . As a protease inhibitor of neutrophil elastase, ulinastatin can alleviate pulmonary edema, hemorrhage, and inflammatory exudation in acute lung injuries through mitigation of the inflammatory reaction and inhibition of immunosuppression …”
Section: Discussionmentioning
confidence: 84%